(untitled) (Global Journal of Medical Research, 2013)
Backgrounds: The objective of the present study was to compare the postoperative analgesic effects of pre-emptive intravenous (IV) paracetamol, lornoxicam and placebo following third molar surgery. Materials and Methods: This was a prospective, double-blind, randomized, placebo-controlled study where 50 patients had both of their identical impacted mandibular third molars impacted. Before the removal of the impacted third molar tooth on one side either of the two drug regimens (1g paracetamol or 8 mg lornoxicam) administered preemptively and 15 days later second surgical approach was performed but this time for comparison the other drug regimen (which was not chosen initially) was carried out as the preemptive agent; and all of the operations were performed by the same surgeon. Diclofenac sodium up to 75 mg daily was provided as rescue medication. The postoperative rescue analgesic consumption was recorded and pain scores were evaluated with a Verbal Rating Scale (VRS) at 15,30 min and 1,2, 4, 6, 12, 24 h postoperatively. Results: There was a significant difference in mean second hour VRS scores between paracetamol and lornoxicam group in favor of the lornoxicam (p